Influence of El Niño Wind Stress Anomalies on South Brazil Bight Ocean Volume Transports. (3rd February 2015) - Assad, Luiz Paulo de Freitas; Böck, Carina Stefoni; Candella, Rogerio Neder; Landau, Luiz
Abstract : The knowledge of wind stress variability could represent an important contribution to understand the variability over upper layer ocean volume transports. The South Brazilian Bight (SBB) circulation had been studied by numerous researchers who predominantly attempted to estimate its meridional volume transport. The main objective and contribution of this study is to identify and quantify possible interannual variability in the ocean volume transport in the SBB induced by the sea surface wind stress field. A low resolution ocean global circulation model was implemented to investigate the volume transport variability. The results obtained indicate the occurrence of interannual variability in meridional ocean volume transports along three different zonal sections. These results also indicate the influence of a wind driven large-scale atmospheric process that alters locally the SBB and near-offshore region wind stress field and consequently causes interannual variability in the upper layer ocean volume transports. A strengthening of the southward flow in 25°S and 30°S was observed. The deep layer ocean volume transport in the three monitored sections indicates a potential dominance of other remote ocean processes. A small time lag between the integrated meridional volume transports changes in each monitored zonal section was observed.